Establishing regional cultivating districts on the basis of the Kreybig practical soil mapping system - Nagy, János; Németh, Tamás; Szabó, József; Pásztor, László; Dobos, Attila (Acta Agraria Debreceniensis, 2001)
With the help of this report evaluating the current situation of the region, characteristics of the development in agricultural production and regional differences can be clarified. By mapping out the regional soil, land use and climatic conditions and organizing these into a geographical information system, one can easily determine which plants are the most ideal to cultivate in that particular region. Moreover, it is a useful tool that enables us to establish the most favorable land use structure suited to ecological demands and also helps to determine the methods of soil protection. During our work, we chose administrative units in Szabolcs-Szatmár-Bereg County, based on the latest aspects of regional cultivation. Our pilot areas are: the small regions of Nyíregyháza, Nyírbátor, Nagykálló, Mátészalka and Csenger. Using the database, we separated and uncovered the soil conditions of the pilot areas: the chemical and physical properties of the soil layer which is exploited by the roots of the plants, the humus content, the nutrient supply, the thickness of the cultivated layer and the water management conditions. We separated the districts of regional cultivation, where the basic elements of the traditional Kreybig color systems were applied (light yellow, dark yellow, light brown, dark green, blue, pink, red, gray, greenish brown, reddish purple, light purple, dark purple, light green). By using the data collected from the pilot areas, we compiled a map database, which is suitable to illustrate the plant cultivating characteristics of the region. We made recommendations to determine the most favorable plants to cultivate in the specific region with the given meteorological and soil conditions, as well as for the shifting of crops. Our recommendations were also illustrated in a map with a resolution of 1:25000.